Energy branding : harnessing consumer power - Larsen, Friðrik (Palgrave Macmillan, 2017)
'An in-depth examination of the modern energy consumer that represents a landmark step forward in energy branding and marketing.' --Kevin Lane Keller, E.B. Osborn Professor of Marketing, Tuck School of Business at Dartmouth College, USA 'Fridrik offers a unique approach to create value for the utilities and their customers.' --Jim Rogers, retired CEO, Duke Energy Demonstrating the potential of building strong brands in the energy sector, this book explores the challenges of shifting the perception of energy from a commodity business into a consumer brand. Energy suppliers are increasingly being met with skepticism, indicating the need for a greater focus on marketing and branding in the energy industry. The author examines both perspectives of energy as a commodity business and a consumer brand, as well as the perception of energy consumers across Europe. Topics discussed include green energy, the liberalization of the electricity industry, and the relationship between consumers and executives in the energy market. One of the first of its kind, this book offers a unique and innovative study of the development of branding in the energy industry, and sheds light on future marketing strategies.
Keywords: Branding (Marketing); Electric utilities -- Marketing.; Energy industries -- Marketing.; Power resources -- Marketing.; elektronické knihy; electronic books